Assessing the state of the lower level of the trophic web of a temperate lagoon, in situations of light or nutrient stress: a modeling study - Lopes, José Fortes
The main purpose of this study is to assess the state of the lower level of the trophic web of a temperate lagoon, the Ria de Aveiro (Portugal), in situations of light or nutrients limitation conditions, that may occur during extreme weather events (eventually associated to climate changes). The increase of the occurrence of extreme events (frequency, intensity and duration) is likely to globally intensify the lagoon turbidity, reducing the depth of light penetration into the water column and shifting the light limitation condition, and therefore reducing phytoplankton biomass and activity. In addition, a scenario of mean river's flow and/or nutrient input decrease may induce a decline of overall phytoplankton biomass and productivity. To research the combined effects of these processes an ecological/eutrophication model was developed and applied for the Ria de Aveiro, dealing with the basic aspects of the lower trophic status of the water column, integrating the nutrient cycling and the main phytoplankton processes. A set of scenarios was designed in order to evaluate the response of the Ria de Aveiro to extreme events, with special emphasis on cases of high precipitation or run-off situations generating high turbidity conditions inside the lagoon, or dry situations or low run-off conditions corresponding to a reduction of the mean precipitation and rivers discharge. Results show that changes in light or nutrients availability may seriously modify the actual lower level state of the lagoon trophic level. Specifically, the occurrence of extreme events in the lagoon ecosystem will shift the lagoon to a light limitation condition, whereas reduction of the rivers discharge will change the nutrients availability, shifting the lagoon to a nutrient limitation condition.